Influence of HIV and HCV on T cell antigen presentation and challenges in the development of vaccines - John, Mina; Gaudieri, Silvana (Frontiers in Microbiology, 2014)
Some of the central challenges for developing effective vaccines against HIV and hepatitis C virus (HCV) are similar. Both infections are caused by small, highly mutable, rapidly replicating RNA viruses with the ability to establish long-term chronic pathogenic infection in human hosts. HIV has caused 60 million infections globally and HCV 180 million and both viruses may co-existent among certain populations by virtue of common blood-borne, sexual or vertical transmission. Persistence of both pathogens is achieved by evasion of intrinsic, innate and adaptive immune defenses but with some distinct mechanisms reflecting their differences in evolutionary history, replication characteristics, cell tropism and visibility to mucosal versus systemic and hepatic immune responses. A potent and durable antibody and T cell response is a likely requirement of future HIV and HCV vaccines. Perhaps the single biggest difference between the two vaccine design challenges is that in HCV, a natural model of protective immunity can be found in those who resolve acute infection spontaneously. Such spontaneous resolvers exhibit durable and functional CD4+ and CD8+ T cell responses. However frequent re-infection suggests partial or lack of protective immunity against heterologous HCV strains, possibly indicative of the degree of genetic diversity of circulating HCV genotypes and subtypes. There is no natural model of protective immunity in HIV, however studies of “elite controllers”, or individuals who have durably suppressed levels of plasma HIV RNA without antiretroviral therapy has provided the strongest evidence for CD8+ T cell responses in controlling viremia and limiting reservoir burden in established infection. Here we compare and contrast the specific mechanisms of immune evasion used by HIV and HCV, which subvert adaptive human leucocyte antigen (HLA)-restricted T cell immunity in natural infection, and the challenges these pose for designing effective preventative